Immune Protection Against Chlamydia trachomatis in Females - Richard P. Morrison (Hindawi Limited, 1996)
Despite significant advances in our understanding of the biology and antigenic structure of Chlamydia trachomatis, and the epidemiology and clinical spectrum of chlamydial disease, the magnitude of morbidity from human chlamydial infections remains an important public health concern. Control of chlamydial disease will likely depend on a multidisciplinary approach, including the development of immunoprophylactic or immunotherapeutic strategies. Reasonable progress has been made in understanding specific immune mechanisms that contribute to host immunity in experimental models of chlamydial infection. However, studies of human immunity have not been so successful. This is particularly evident in that studies to address the development and role of mucosal immune responses to urogenital chlamydial infections have not been forthcoming. The following review is a brief summary of our current knowledge of protective immunity to chlamydial urogenital infections of females. It is not meant to be exhaustive, but instead to touch upon aspects of protective immunity that have been described in both human and experimental animal models of chlamydial infection.